SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN GURU BARU PADA TK WALADUN SHOLIHUN MENGUNAKAN METODE TOPSIS - Yuli Praptomo PHS; Siti Rahayu (Jurnal Informatika Komputer, Bisnis dan Manajemen, 2021)
The process of selecting new teacher recruitment at Tk Waladu Sholihun generally still uses a manual system, where the determination is based on an assessment of 5 missing criteria, using a computerized system, resulting in inaccurate or less maximal problems arising by the school and in selecting recruitment new teacher.The system that will be used to perform analysis and research is using the TOPSIS method. The criteria used in determining decision making are work experience, ability test, interview test, latest education, age. The Decision Support System determines the acceptance of this new teacher based on the desktop using the PHP programming language and the MySQL database as data storage.This system produces the best choice of teacher selection from the alternative options produced. The final result of the TOPSIS method produces the best alternative choice that is determined. This system makes the process of determining the selection of new teacher recruitment computerized